V. – Tony Harrison’s Poetic Dialectic - Klepuszewski, Wojciech (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2011)
Tony Harrison’s long poem v. published in 1985, and televised by Channel Four in 1987 was a milestone in his literary career, not only because of the reception it received, but also because Harrison managed to use poetry as an effective tool for a debate concerning important social issues
Keywords: Harrison; Poem